Who will feed China in the 21st century?: Income growth and food demand and supply in China - Fukase, Emiko; Martin, Will (Wiley, 2016)
This study uses resource‐based measures to explore the evolution of China's demand and supply for food. China's dietary shift from plant to animal‐based foods, induced by its income growth, is likely to impose considerable pressure on agricultural resources. China's demand for food on this measure appears consistent with global trends, while China is an out‐performer on the supply side, producing much more food than its income level and land endowment would predict. China's current per capita income is in a range where consumption growth is high and in excess of production growth, but the gap between supply and demand is likely to diminish as population and per capita consumption growth decelerate. Continuing agricultural productivity growth and sustainable resource management will be important influences on the growth of China's future net import demand for food.